2013
DOI: 10.1002/jbm.a.34758
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect between bioactive glass foam and a perfusion bioreactor on osteogenic differentiation of human adipose stem cells

Abstract: Tissue engineering is a multidisciplinary science that combines a structural scaffold and cells to form a construct able to promote regeneration of injured tissue. Bioactive glass foam produced by sol-gel is an osteoinductive material with a network of interconnected macropores necessary for cell colonization. The use of human adipose-derived stem cell (hASC) presents advantages as the potential for a large number of cells, rapid expansion in vitro and the capability of differentiating into osteoblasts. The us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 62 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…Indeed bmMSC cultured on different porous hydroxyapatite scaffolds (total porosity in vol%: 37, 44, and 90) for 17 days have shown an increase of osteogenic differentiation with an increase of porosity . Related studies have been carried out recently on scaffolds based on bioactive glass‐polycaprolactone composites produced by robotic dispensing technique which were seeded with adMSC . After 4 weeks of dynamic perfusion, differentiation of the cells was confirmed by alkaline phosphate expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed bmMSC cultured on different porous hydroxyapatite scaffolds (total porosity in vol%: 37, 44, and 90) for 17 days have shown an increase of osteogenic differentiation with an increase of porosity . Related studies have been carried out recently on scaffolds based on bioactive glass‐polycaprolactone composites produced by robotic dispensing technique which were seeded with adMSC . After 4 weeks of dynamic perfusion, differentiation of the cells was confirmed by alkaline phosphate expression.…”
Section: Resultsmentioning
confidence: 99%
“…39 Related studies have been carried out recently on scaffolds based on bioactive glass-polycaprolactone composites produced by robotic dispensing technique which were seeded with adMSC. 40 After 4 weeks of dynamic perfusion, differentiation of the cells was confirmed by alkaline phosphate expression.…”
Section: In Vitro Analysismentioning
confidence: 99%
“…Recently, Silva and colleagues [34] demonstrated that human ADSCs differentiate towards the osteogenic phenotype when cultured in a bioactive glass scaffold as indicated by significant increase in cell proliferation and viability, along with increased ALP activity and the expression of osteospecific proteins such as osteocalcin and osteopontin. One of the major limitations of such cellular growth on scaffolds is the lack of angiogenesis.…”
Section: Adipose Tissue-derived Stem Cellsmentioning
confidence: 99%
“…The major substrates are hydroxyapatite, tricalcium phosphate, and biphasic calcium phosphate [26]. While capable of inducing osteoblastic differentiation in-vitro, they are typically too brittle and resorb too slowly to be practical for bone grafting applications [27].…”
Section: Bioactive Ceramics Bioactive Glass and Hydrogelsmentioning
confidence: 99%